Correlation Between Coronary Lesion Severity Detected in Fractional Flow Reserve with Systemic Immune Inflammation Index and Atherogenic Plasma Index - Tuncay Güzel; Mehmet Kış (Bagcilar Medical Bulletin, 2022)

(untitled)
Objective:Systemic immune inflammation index (SII) and atherogenic plasma index (AIP) are indices that have been defined in recent years and play an important role in the process of atherosclerosis and inflammation. In this study, we aimed to investigate the relationship between the severity of atherosclerotic lesions detected and AIP and SII in patients who underwent fractional flow reserve (FFR) in coronary angiography.Method:In this study, 119 patients who underwent elective FFR in coronary angiography were retrospectively analyzed. According to the severity of FFR lesion, two groups were formed as FFR <0.8 group (77 patients) and FFR >0.8 group (42 patients). SII, AIP, demographic data and other parameters were compared between the two groups.Results:In the FFR applied groups, there was a statistically significant difference between the two groups in terms of high-density lipoprotein (p=0.001), platelet (p=0.007), mean platelet volume (MPV) (p=0.016), monocytes (p<0.001), lymphocyte (p<0.001), SII (p<0.001), AIP (p=0.009) and HbA1c (p<0.001). In the univariable regression analysis, we found that HbA1c [odds ratio (OR): 10; 95% confidence interval (CI): 3.2-3.5, p<0.001], monocytes (OR: 273.8; 95% CI: 24.8-3015.3, p<0.001), MPV (OR: 0.6; 95% CI: 0.39-0.91, p=0.02), SII (OR: 1.06; 95% CI: 1.03-1.09, p<0.001) and AIP (OR: 3.7; 95% CI: 1.6-10, p=0.01) parameters were predictors. In the multivariable regression analysis, we found that HbA1c (OR: 9.41; 95% CI: 1.89-46.73, p=0.006), monocytes (OR: 108.2; 95% CI: 6.8-1726.2, p=0.001) and SII (OR: 1.005; 95% CI: 1.002-1.008, p=0.004) parameters were independent predictors. With the applied ROC analysis, SII predicted FFR lesion severity with 75% sensitivity and 72% specificity [area under the curve (AUC): 0.79; 95% CI: 0.72-0.87, p<0.001], and AIP with 62% sensitivity and 60% specificity (AUC: 0.64; 95% CI: 0.54-0.75, p=0.008).Conclusion:In this study, we would like to emphasize that simple, fast and low-cost methods such as AIP and SII may be parameters related to lesion severity detected in FFR. These parameters are easily accessible, reproducible and widely used.